2017
DOI: 10.5937/aaser1744123m
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between milk production and metabolic adaptation in dairy cows during heat stress

Abstract: Abstract:The aim of this study is to determine correlation between change in milk production and metabolic adaptation of cows during heat-stress. Experiment included 30 Holstein-Frisian cows. Cows exposed to heat-stress, which is expressed in high THI index, have lower milk production, higher concentration of insulin and lover concentrations of glucose and NEFA. Indexes of insulin resistance-RQUICKI, insulin: glucose and insulin: NEFA relations are higher in cows under heat stress. Grouping cows in accordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…With regard to the response of increasing RR, Kadzere et al (2002) reported that about 15% of accumulated metabolic heat is dissipated by the respiratory tract for evaporative heat loss under hot conditions. Heat stress occurs when a cow is exposed to T that exceed her biological thermal comfort zone and has to make a lot of effort (and may even fail to) dissipate enough heat to maintain her body thermal balance (Majkić et al, 2017). Li et al (2020) reported that the rectal temperature (RT) of a high-producing cow started to increase when the ambient T was above 20.4°C.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the response of increasing RR, Kadzere et al (2002) reported that about 15% of accumulated metabolic heat is dissipated by the respiratory tract for evaporative heat loss under hot conditions. Heat stress occurs when a cow is exposed to T that exceed her biological thermal comfort zone and has to make a lot of effort (and may even fail to) dissipate enough heat to maintain her body thermal balance (Majkić et al, 2017). Li et al (2020) reported that the rectal temperature (RT) of a high-producing cow started to increase when the ambient T was above 20.4°C.…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress is an important factor affecting insulin sensitivity in dairy cows. Results (Majkić et al, 2017) showed that: a) Cows exposed to heat-stress (high THI index) have lower milk production, higher concentrations of insulin and lower concentrations of glucose and NEFA; b) indices of insulin resistance-RQUICKI, insulin:glucose and insulin:NEFA are higher in cows under heat stress. The decrease in glucoses followed by an increased insulin level and increased insulin sensitivity indicate that glucose is transferred from the udder to other tissues, which can cause decreased milk production.…”
Section: Insulin Resistance Definition and Pathogenesismentioning
confidence: 99%
“…Lohi sheep account for 40% of national sheep production. Oxidative stress determination is the best tool for improved reproductive performance in sheep (El-Ratel et al, 2020) and cows (Majkić et al, 2017). As no significant information is available in the literature on Lohi sheep [48] on the physiological biomarkers concerning pregnancy and production at different stages, it is being hypothesized that these biomarkers during different stages of pregnancy and production will behave quite differently.…”
Section: Introductionmentioning
confidence: 99%